Investigation On Titanium Dioxide Nanotubes Photoanode For Dye Sensitized Solar Cell Application - Cheong, Yuit Ling (2018)
This study primarily focused on the synthesis of titanium dioxide (TiO2) nanotubes (NTs) and the improvement of the TiO2-based dye-sensitized solar cell (DSSC) by components optimization. Titanium foil with sandpolish surface treatment was chosen to grow NTs due to its simplicity and even surface for the synthesis of NTs. TiO2 NTs were grown via various types of electrochemical anodization methods such as one-step, two-step, alternating voltage and fast anodization methods. For one and two-step anodizations, diameter and length of NT increased linearly with the applied voltage. However, the top view morphology of samples anodized by these methods was differed. In addition to that, NT length was not increased monotonously with anodization duration.